Development of a model system to describe the flavor of grain varieties and a sensory lexicon to describe the flavor of sorghum - Thao, Nguyen Phuong Tran (Kansas State University, 2018)
Sorghum (Sorghum bicolor [L.] Moench), is an ancient grain that possesses many health and economic values. Understanding the differences in the flavor profiles among cultivars is essential to increase the usage of the grain for food application purposes. The main objectives of this study were to 1) develop a model system to taste grain varieties and 2) develop a sensory lexicon to describe the flavor profile of sorghum grains. Fifty-seven sorghum cultivars including US commercially available samples as well as important breeding lines from around the world were included and investigated in the study. After thorough investigations, this study developed a model which includes cooked grain and cookie applications to facilitate flavor characterization among different cultivars. The cooked grain and cookie recipes developed in this project are neutral and consistent. Therefore, they can serve as systems prototypes for identification of a grain’s flavor profile and support descriptive analysis studies of flavor among grain cultivars. The developed model has been applied in sorghum and wheat to successfully characterize the flavor profile among different cultivars. Moreover, a sensory lexicon with 28 descriptive terms was developed by the trained panel to describe the flavor of sorghum in grain form and in finished products. Some of the terms in the lexicon were starchy, beany, cardboard, oil-heated, brown-sweet, buttery, umami, overall green, musty dusty, woody, wheat like, sweet, salty, sour, bitter and metallic. Each attribute has a descriptive definition to describe the term and two to three descriptive references. The panel validated the effectiveness of the developed lexicon using a set of 20 sorghum cultivars, which were presented to the panelists in two forms: cookies and cooked grains. The descriptive analysis results were analyzed using PCA to produce sensory maps with key attributes associated with each sample. The generated maps for both cooked grain and cookies application showed clear differentiation in flavors among sorghum cultivars indicating that the lexicon can be used to effectively characterize sorghum’s flavors in multiple applications. Such understanding will help to support researchers, food producers, food manufacturers and contribute to promoting the use of sorghum grains in food applications.
Keywords: Sorghum; Sorghum flavor; Lexicon development; Sensory; Grain flavor